The immediate effects of kinesio taping on lumbar range of motions / Mohd Haidir MY, Fatimah M Rom and Kandasamy G - MY, Mohd Haidir; M Rom, Fatimah; G, Kandasamy (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
This study aims at determining the initial effects of kinesio taping (KT) applied to erector spinae muscle on lumbar flexion, extension and lateral flexion range of motions (ROM). Pre-post parallel controlled trial study was conducted on twenty healthy subjects divided equally into two groups (KT and placebo). Lumbar spine flexibility was evaluated using tape measure method for all lumbar tested motions. KT group showed significantly improve lumbar flexion ROM, yielded an increment of 9.9 cm compared with placebo group (9.9 cm, t (9) = -4.265, p = 0.002). However, no significant differences were discovered for lumbar extension (-0.9 cm, t (9) = 1.132, p = 0.287), right lumbar lateral flexion (1.2 cm, t (9) = -1.964, p = 0.081) and left lumbar lateral flexion ROM (0.8 cm, t(9) = -1.633, p = 0.137). The ANCOVA adjusted change scores revealed that the KT group demonstrated a very large effect size in lumbar flexion ROM. Meanwhile, trivial and moderate effect sizes were identified in lumbar extension and lateral flexion ROM respectively. Hence, the KT positively influences erector spinae muscle, allowing improvements in the active lumbar flexion ROM immediately after the application of KT.